TOWARDS THE FORMATION OF THE NOTION OF EMOTIONAL CULTURE OF TRANSLATOR’S LINGUISTIC PERSONALITY IN THE DIPLOMATIC DISCOURSE - N.Y. Georgieva; N.G. Korshunova (Многоязычие в образовательном пространстве, 2023)
The relevance of the article is caused by anthropocentrism of modern translation studies. This study examines the translator’s linguistic personality and describes their professional competencies (hard skills) and extra-professional competencies (soft skills). Special attention is paid to the translator’s emotional competence in diplomatic discourse. The study aims to identify the translator’s emotionality in the process of translating diplomatic texts. To achieve the goal the methods of analysis, generalisation and comparative analysis were used. The research findings suggest that emotionally coloured vocabulary may present difficulties when translating a text in diplomatic discourse. In order to overcome these difficulties, it is necessary to develop the emotional culture of the translator’s linguistic personality.